2020
DOI: 10.1038/s41598-020-78701-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of low-head hydropower plants on cyprinid-dominated fish assemblages in Lithuanian rivers

Abstract: The meso-scale habitat simulation model MesoHABSIM was applied in three Lithuanian lowland rivers to study the effect of low-head hydropower plants (HPPs) on the fish habitats. Stream flow time series on a daily scale for the period 1970–2015 were used to describe flow regime downstream of HPPs for periods before and after their installation. Conditional habitat suitability criteria were developed for 4 species of cyprinid fish, schneider (Alburnoides bipunctatus), dace (Leuciscus leuciscus), roach (Rutilus ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, no clear trends in the changes of minimum flows were identified. Virbickas et al [16] analyzed the impact of three HPPs (Skuodas, Kuodžiai, and Dvariūkai, i.e., the same as in the present study) on fish habitats in downstream river stretches in the warm period. The analysis revealed that at the extremely low flows, the studied stretches became unsuitable or only partly suitable for studied fish species.…”
Section: Discussionmentioning
confidence: 95%
“…However, no clear trends in the changes of minimum flows were identified. Virbickas et al [16] analyzed the impact of three HPPs (Skuodas, Kuodžiai, and Dvariūkai, i.e., the same as in the present study) on fish habitats in downstream river stretches in the warm period. The analysis revealed that at the extremely low flows, the studied stretches became unsuitable or only partly suitable for studied fish species.…”
Section: Discussionmentioning
confidence: 95%
“…Two additional WGSs of Dubysa-Lyduv ėnai (for the Širvinta and Šešup ė rivers) and Minija-Kartena (for the Bartuva River) were selected for the restoration of natural conditions of river discharge at selected river stretch. The selection of a river analog was based on a similar catchment area, similarity in physico-geographical and hydrometeorological characteristics, and absence of anthropogenic structures, which could interrupt the continuity of the river, e.g., dams [39]. The regression equations between analyzed rivers and river-analog were created using daily discharge data before the date of HPPs construction (Table 1).…”
Section: Evaluation Of Hydrological Characteristicsmentioning
confidence: 99%
“…Conditional habitat suitability criteria (CHSC) have previously been developed for 4 fish species: roach, dace, schneider, and vimba [39]. For the remaining species, within the current study, new CHSC were developed (Appendix A, Table A1) and validated using the same method [39].…”
Section: Fish Habitat Models and Impact Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain river functions (biological habitats, material exchanges, natural landscapes, etc. ), governments generally require reservoir managers to control the discharge based on the recommended environmental flow (Turgeon et al 2021), which is often determined by hydrology methods, hydraulics methods, habitat simulation methods and holistic methods (Goguen et al 2020). However, these methods ignore the importance of runoff flood pulses, because the recommended environmental flow are determined from the base flow (the minimum flow that meets the basic ecological function of the river) and the fixed value (Lobera et al 2021).…”
Section: Introductionmentioning
confidence: 99%